United Republic of Tanzania Systematic Country Diagnostic : To the Next Level of Development - World Bank Group (World Bank, Washington, DC, 2017)
Tanzania began its independence as a socialist country, but in the 1980s economic difficulties pushed it to adopt macroeconomic reforms, among them removing direct controls on prices and exchange and interest rates and opening up industry to private investment. Reforms intensified in the second half of the 1990s with steep cuts in public spending, which helped the Government to move from fiscal deficits to surpluses. Inflation was brought under control. Exchange rate stability was restored, and the Government carried out structural reforms to boost exports, liberalize domestic markets, and reduce public sector involvement in the economy. This Systematic Country Diagnostic (SCD) provides an informed and integrative perspective on what Tanzania can do to move its national goals forward. The primary aim of the SCD is to analyze the country’s current opportunities and challenges and identify priority areas for policy action. The findings will be the foundation for the Country Partnership Framework (CPF), which will guide the engagement of the World Bank Group (WBG) with Tanzania for the next five years. The SCD builds on a wide range of analyses conducted by the WBG, the Government, and other institutions. The World Bank’s Country Economic Memorandum (CEM) 2014 and poverty assessment 2015 have contributed to the diagnostic, and the Policy Notes for the New Administration, presented in December 2015, helped set the sector-specific policy agenda and informed the analysis of binding constraints and potential solutions. Consultations for the SCD brought in a broad range of stakeholders.